(untitled) (LACCEI, 2024)
This research aimed at developing a specialized social platform for individuals affected by cancer. The goal was to improve their quality of life and promote prevention through the sharing of experiences and knowledge, fostering a prevention culture. The main content management systems (CMS) available in the market were analyzed, and WordPress was selected for the development of the platform, along with the development of a specific methodology for the project. The results showed a positive impact on the quality of life of the patients. The users who actively participated in the platform, by consulting or sharing posts and comments, experienced a significant increase in their knowledge and understanding of topics related to cancer prevention and care, allowing them to apply this knowledge to decision-making for other patients.